Beautiful yesterdays / Mumtaz Mokhtar - Mokhtar, Mumtaz (Faculty of Art and Design, 2021)
The work entitled Beautiful Yesterdays is the artist's reflection on the latest issue of Israelis' attack on Palestinians. The grievances of the Palestinian people demand universal peace and a prosperous life to be given back as they once sang. This is clear from the verses of Atouna ElToufoule's song. Innocent children are entitled to a prosperous life like other children around the world. Not only children but all their citizens want the happiness they have enjoyed before such as happiness before adversity, health before illness and strong before suffering. In addition, the background of the story revolves around the Al Aqsa Mosque which is represented by its coordinates and needs to be defended as a historical location giving a very beautiful picture of the historical story of prophet Rasulullah SAW. This is a beauty that should be remembered by every Muslim in the world.